Polygamy in Islamic Law and Contemporary Muslim Societies: A Maqāṣid-Oriented Systematic Review - Aida Humaira; Nabiilah Ar Rasyidah; Rizkika Tiara Rahmani; Ananda Bintang Kelana (Jurnal Fuaduna : Jurnal Kajian Keagamaan dan Kemasyarakatan, 2025)
This study aims to critically examine the concept and practice of polygamy within Islamic law and contemporary legal frameworks in Indonesia and selected Muslim countries, with particular attention to justice, protection of women and children, and the objectives of Sharīʿah (maqāṣid al-sharīʿah). Although polygamy is normatively permitted in Islam based on Qur’anic texts, its application frequently reveals a significant gap between ideal legal norms and empirical realities, often resulting in gender inequality and socio-psychological harm. Employing a qualitative design, this research adopts a Systematic Literature Review (SLR) guided by the PRISMA framework, combined with socio-legal doctrinal and comparative approaches. Data were drawn from peer-reviewed journal articles, Islamic legal literature (classical and contemporary), statutory regulations, and empirical studies from various Muslim contexts, including Indonesia, Turkey, Tunisia, Pakistan, Saudi Arabia, Afghanistan, and India. The findings demonstrate that polygamy in Islamic law functions as a conditional legal dispensation (rukhṣah), rather than an ideal marital model, and is strictly contingent upon the fulfillment of substantive justice and public benefit (maṣlaḥah). This study further classifies polygamy practices into best practices and bad practices, revealing that unregulated and clandestine polygamy often leads to legal insecurity, economic inequality, and psychological vulnerability. The article concludes that a maqāṣid-oriented interpretation, coupled with strong legal enforcement and ethical responsibility, is essential to minimizing harmful polygamy practices and safeguarding vulnerable family members.